Clinical characteristics of patients with Lupus Nephritis in a tertiary care hospital in Malaysia– A cross sectional study - Wahinuddin Sulaiman; Nik Syamim Firdaus Nik Ahmad Zuky; Muhammad Faris Mhd Ali; Meor Fazrul Hanif Meor Azam; Nur Nazifah Mohd Farid; Loh Chek Loong; Sandheep Sugathan (Asian Journal of Medicine & Health Sciences, 2021)
Introduction: Lupus nephritis (LN) is a common complication as evidenced clinically in 50-60% of patients with systemic lupus erythematosus (SLE) and is present histologically even in patients, without obvious symptoms of renal disease. Evaluating renal function in SLE patients is important because early detection with prompt treatment of renal involvement can significantly improve the prognosis. Methods: The is a single-center cross-sectional study conducted in 2019 which included data regarding 235 LN patients from a tertiary nephrology clinic at Hospital Raja Permaisuri Bainun Ipoh, Perak, Malaysia. Basic clinical and demographic data for all LN patients were retrieved and analyzed from outpatient clinical records. Results: A total of 235 LN patients with female to male ratio of 10:1. Ethnic stratification analysis showed that LN was highest in Malay ethnic group (49.4%, n=116) followed by Chinese (42.1%, n=99) and Indian (4.3%, n=10). The median age and duration of the disease were 41 (40 – 43) years and 5 (6 – 8) years respectively. Nephrotic presentation was significantly higher than nephritic presentation among all classifications of LN patients. Positive ANA and dsDNA with low C3 and C4 were frequently present in Class IV patients. Conclusion: Proliferative lupus nephritis was the most common diagnosis amongst those who presented in our study cohort. The clinical and renal manifestations were relatively homogenous, although vary in frequency throughout different classes of LN. Multi-ethnicity with varies genetic background may contribute to the wide spectrum of LN phenotypes which need to be studied in future.